A Survey of Speech-Language Pathologists in the WI Birth-3 Program - Albers, Kathryn; Cable, Emily; Foley, Bridget; Kallstrom, Allison; Milanowski, Jamie; Pieper, Morgan; Schaub, Kyla (My University, 2012)
The goal of this study was to discover whether speech-language pathologists, working in the Wisconsin Birth to Three Program, serve children with speech sound delays.
Color poster with text, maps, and tables.
Keywords: Educational surveys--Wisconsin; Speech therapists--Wisconsin; Birth to Three Program (Wis.); Posters